Projeto e implementação de um serviço de interpretação de contexto em apoio à preparação e resposta a emergências - Campos, Marcio Roberto de (Universidade Federal de São Carlos, 2009)
In this MSc project an interpretation service was designed and implemented containing a knowledge base built from the integration of ontologies and a fuzzy inference system. Besides interpreting what is occurring in the environment, the main feature of this service is to provide additional information on the phenomenon being observed, such as neighboring risks. The knowledge base was generated with the help of experts in the field of emergency preparedness and response. For the real-time monitoring to be effective it is necessary that the data captured by sensors from the physical environment be interpreted in a fast and accurate way. Context interpretation can be either simple when handling information ambiguities and replication or highly complex when different contexts and events correlation are involved. Wireless sensors networks are increasingly being used as powerful tools for the monitoring of environments subject to life and assets risk situations, such as fires, toxic gas leaks and explosions. Emergency management systems that incorporate wireless sensor networks are being used to support emergency first responders in the decision making process where response time is crucial for the success of rescue operations. To validate the proposed interpretation service, implemented as a tool to aid in emergency situations, a use case was built using a local company plant. The context interpretation service built from the integration of ontologies and fuzzy techniques has shown to be a potential aid tool for the monitoring of physical environments subject to emergency situations
Keywords: Sistema difuso; Interpretação de contexto; Fuzzi logic; Ontologia; Gerenciamento da emergência; Context Interpretation; Fuzzy; Ontology; Emergency Management; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO